Silicon mitigates K deficiency in maize by modifying C, N, and P stoichiometry and nutritional efficiency - Costa, Milton Garcia [UNESP]; de Mello Prado, Renato [UNESP]; dos Santos Sarah, Marcilene Machado [UNESP]; de Souza, Antônia Erica Santos [UNESP]; de Souza Júnior, Jonas Pereira [UNESP] (Springer Nature, 2023)
Potassium (K) deficiency in maize plants damages the nutritional functions of K. However, few studies have investigated the influence of K on C:N:P stoichiometry, the nutritional efficiency of these nutrients, and whether the mitigating effect of Si in plants under stress could act on these nutritional mechanisms involved with C, N, and P to mitigate K deficiency. Therefore, this study aimed to evaluate the impact of K deficiency in the absence and presence of Si on N and P uptake, C:N:P stoichiometric homeostasis, nutritional efficiency, photosynthetic rate, and dry matter production of maize plants. The experiment was conducted under controlled conditions using a 2 × 2 factorial scheme comprising two K concentrations: potassium deficiency (7.82 mg L−1) and potassium sufficiency (234.59 mg L−1). These concentrations were combined with the absence (0.0 mg L−1) and presence of Si (56.17 mg L−1), arranged in randomized blocks with five replicates. Potassium deficiency decreased stoichiometric ratios (C:N and C:P) and the plant’s C, N, and P accumulation. Furthermore, it decreased the use efficiency of these nutrients, net photosynthesis, and biomass of maize plants. The results showed that Si supply stood out in K-deficient maize plants by increasing the C, N, and P accumulation. Moreover, it decreased stoichiometric ratios (C:N, C:P, N:P, C:Si, N:Si, and P:Si) and increased the efficiencies of uptake, translocation, and use of nutrients, net photosynthesis, and dry matter production of maize plants. Therefore, the low nutritional efficiency of C, N, and P caused by K deficiency in maize plants can be alleviated with the supply of 56.17 mg L−1 of Si in the nutrient solution. It changes C:N:P stoichiometry and favors the use efficiency of these nutrients, which enhances the photosynthesis and sustainability of maize.